Biodiversity of benthic macroinvertebrates in Air Terjun Lata Kinjang, Chenderiang, Perak, Malaysia - Nurhafizah-Azwa Abdul Satar,; Ahmad Abas Kutty,; Hanisah Ibrahim, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
A study on benthic macroinvertebrate diversity was conducted in Air Terjun Lata Kinjang, Chenderiang, Perak, Malaysia. Five stations were selected with a distance of approximately 500 metre interval. Three replicates of benthic macroinvertebrates and water samples were taken from each station. Result indicates that Air Terjun Lata Kinjang is in class I condition based on Malaysian water quality index. A total of two phyla, three classes, eight orders, 30 families, and 1177 individuals were successfully identified. The average Shannon Diversity Index, (H’) is 2.07, Pielou Evenness Index, (J’) is 0.46, and Margaleff Richness Index, (DMg) is (3.08). These values describe Air Terjun Lata Kinjang as in good conditions but macroinvertebrates are not uniformly distributed between stations. Biological Monitoring Working Party (BMWP) and Family Biotic Index (FBI) score are 150 and 4.75, respectively which also explain this stream as having good water quality. The CCA test was conducted to show environmental factors towards benthic macroinvertebrate distribution. The presence of Baetidae with a high abundance of the families shows the potential to be used as biological indicators of a clean ecosystem.